Corporate Governance and Sustainability: The European experience of profit companies and their potential in Latin American corporate law - Valero Palomino, Fiorella Rocío; Bullón-Solís, Omar; Méndez-Gutíerrez, Leidy Lucía; Bullón-Solís, Nadia; Solís-Castro, Alex Omar; Silva-Medina, Walter (LACCEI, 2025)
The study develops the experience of the regulation of benefit companies in the European experience, especially the Italian and French ones, to glimpse their possible incorporation into the law of Latin American companies. Using a qualitative and legal-comparative approach, standards such as società benefit, société à mission or the new European directives on sustainable sustainability are studied. The results of the work conclude that Europe has been able to legally incorporate sustainability into governance, while Latin America is characterized by a voluntarist, undemanding and rather declarative approach, it is concluded that the European model can be transferred to the region, although with its own institutional and cultural particularities, in order to be able to provide itself with a legal framework that guarantees sustainable entrepreneurship with a correct sufficiency of the Corporate responsibility.